2021
DOI: 10.1155/2021/5578629
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Mechanical Characteristics of Cyclic Loading and Unloading of Rock Based on Infrared Thermal Image Analysis

Abstract: In the operations of underground rock engineering, such as mining, the formation of goafs is often accompanied by unloading and energy effects. In this study, a cyclic loading and unloading stress test is carried out to analyze the strength characteristics of the loaded samples under different loading and unloading ranges as well as different numbers of cycles. The rock force is accompanied by substantial energy changes. To better fit the energy analysis under cyclic loading and unloading conditions, thermal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…In terms of acoustic emission characteristics of rocks during uniaxial cyclic loading and unloading, C. Li showed that not all types of rocks are subject to the Kaiser effect [3]. L. Wu studied the thermal infrared radiation energy characteristics of granite under cyclic loading and unloading conditions [4]. M. Zhang pointed out that increasing the loading and unloading rate will reduce the total acoustic emission ring of red sandstone samples, and the total acoustic emission count of rock samples has a negative linear relationship with the loading and unloading rate [5].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of acoustic emission characteristics of rocks during uniaxial cyclic loading and unloading, C. Li showed that not all types of rocks are subject to the Kaiser effect [3]. L. Wu studied the thermal infrared radiation energy characteristics of granite under cyclic loading and unloading conditions [4]. M. Zhang pointed out that increasing the loading and unloading rate will reduce the total acoustic emission ring of red sandstone samples, and the total acoustic emission count of rock samples has a negative linear relationship with the loading and unloading rate [5].…”
Section: Introductionmentioning
confidence: 99%